Influence of milling parameters on the sorption properties of the LiH-MgB2 system doped with TiCl3 - Busch, Nina (2014)
Abstract Hydrogen sorption properties of the LiH-MgB2 system doped with TiCl3 were investigated with respect to milling conditions (milling times, ball to powder (BTP) ratios, rotation velocities and degrees of filling) to form the reactive hydride composite (RHC) LiBH4-MgH2. A heuristic model was applied to approximate the energy transfer from the mill to the powders. These results were linked to experimentally obtained quantities such as crystallite size, specific surface area (SSA) and homogeneity of the samples, using X-ray diffraction (XRD), the Brunauer-Emmett-Teller (BET) method and scanning electron microscopy (SEM), respectively. The results show that at approximately 20 kJ g-1 there are no further benefits to the system with an increase in energy transfer. This optimum energy transfer value indicates that a plateau was reached for MgB2 crystallite size therefore the there was also no improvement of reaction kinetics due to no change in crystallite size. Therefore, this study shows that an optimum energy transfer value was reached for the LiH-MgB2 system doped with TiCl3.